Further Investigations into the Regioselectivity of 6,7-Indole Aryne Cycloadditions with 2-Substituted Furans: Remarkable Contrasteric Preference Depends on Pyrrole and Benzene Ring Substitution - Nerurkar, Alok; Chandrasoma, Nalin; Maina, Lincoln; Brassfield, Allen; Luo, Diheng; Brown, Neil; Buszek, Keith R. (Synthesis, 2013)
A series of related 6,7-dibromoindole compounds were prepared to study the effects of pyrrole and benzene ring substitution patterns on the regioselectivity of 6,7-indole aryne cycloadditions with 2-tert-butylfuran. The arynes were generated by our metal–halogen exchange/elimination protocol. The results of this investigation reveal that substitution at the 3-position on the indole ring in particular results in remarkable regiocontrol that favored the contrasteric products. Aromatic conjugation at this site significantly enhanced this effect. However, the presence of most 4- or 5-substituents generally resulted in markedly reduced selectivity. Exceptions in this latter series included the 4-ethyl and 4-iodo cases both of which also gave predominantly contrasteric products even in the absence of a beneficial C-3 substituent.
Keywords: alkaloids; arynes; cycloaddition; indoles; regioselectivity